The solution of 4x - 8 + 3x = 49 - 73 + 4x - 1 + 2 is equal to
![x = (-5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mhykla9kvsfgyi02l16myoznvj8zfr49xy.png)
Solution:
Given, equation is 4x – 8 + 3x = 49 – 73 + 4x – 1 + 2
We have to solve the above given equation for x.
Now, take the given equation.
4x – 8 + 3x = 49 – 73 + 4x – 1 + 2
Adding the like terms we get,
7x – 8 = - 14 + 4x + 1
7x – 4x = - 14 + 1 + 8
3x = - 14 + 9
3x = - 5
![x = (-5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mhykla9kvsfgyi02l16myoznvj8zfr49xy.png)
Hence, the value of x is
![(-5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9g90tas8vvmjjiww3fq63tccljr2rp5e61.png)